2001
DOI: 10.1111/j.1749-7345.2001.tb00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Sac‐Fry and Hatchery‐Fed Fry on Production of Fingerling Channel Catfish Ictalurus punctatus

Abstract: Abstract.— Channel catfish Ictalurus punctatus fry are typically held under hatchery conditions for 7 to 14 d after hatching to allow feeding and growth before they are stocked into nursery ponds to produce fingerling catfish. In an attempt to reduce hatchery operating costs, several catfish fingerling producers in Louisiana presently stock fry within 2 d after hatching before yolk absorption is complete. Fry at this stage of development are commonly referred to as “sac‐fry.” Although research has shown that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
3
5
1
Order By: Relevance
“…Total feed fed also increased with increased survival. In our study, overall survival rates were not as high as those reported by Tidwell et al (1995) (31-86%) or those reported by Weirich et al (2001) (72-92%), but were better than those reported by Reigh et al (2006) (4-13%).…”
Section: Resultscontrasting
confidence: 74%
See 4 more Smart Citations
“…Total feed fed also increased with increased survival. In our study, overall survival rates were not as high as those reported by Tidwell et al (1995) (31-86%) or those reported by Weirich et al (2001) (72-92%), but were better than those reported by Reigh et al (2006) (4-13%).…”
Section: Resultscontrasting
confidence: 74%
“…Neither Tidwell et al (1995) nor Weirich et al (2001) found differences in survival of fingerling catfish stocked as either sac fry or hatchery‐fed fry. However, those studies were done in small 0.04‐ha ponds and 10,000‐L tanks, respectively, which may not represent commercial conditions.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations